The Impact of Artificial Intelligence and Deep Learning in Eye Diseases: A Review - Nuzzi, Raffaele; Boscia, Giacomo; Marolo, Paola; Ricardi, Federico (Frontiers in Medicine, 2021)
Artificial Intelligence (AI) is a subset of computer science dealing with development and training of algorithms that try to replicate human intelligence. We report a clinical overview of the basic principles of AI that are fundamental to appreciate its application to ophthalmology practice. Here, we review the most common eye diseases focusing on some of the potential challenges and limitations emerging with the development and application of this new technology into ophthalmology.